2015
DOI: 10.5944/openpraxis.7.4.249
|View full text |Cite
|
Sign up to set email alerts
|

Validating student satisfaction related to persistence, academic performance, retention and career advancement within ODL perspectives

Abstract: Student satisfaction associated with persistence, academic performance, retention, and its relations to career advancement were examined. It was aimed at measuring service quality (Servqual) dimensions as a foundation of satisfaction and how, in what comportments, they were interrelated. The study was conducted under explanatory-design. Data was collected proportionally and purposively followed by congregating them through unified interviews. Population was 1,814 Universitas Terbuka students domiciled overseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…According to obtained results, quick resolution of complaints by faculty management was a significant predictor of BI. It may be noted that the results obtained in a particular domain coincide with the results of the previously conducted research in which author (Sembiring, 2015) proves that there is an indirect influence of complaints management on persistence and retention of students, through their satisfaction.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…According to obtained results, quick resolution of complaints by faculty management was a significant predictor of BI. It may be noted that the results obtained in a particular domain coincide with the results of the previously conducted research in which author (Sembiring, 2015) proves that there is an indirect influence of complaints management on persistence and retention of students, through their satisfaction.…”
Section: Discussionsupporting
confidence: 84%
“…Out of the total number of questions, 20 of them are directly related to the services (an importanceperformance group of questions), four of them refer to BI, and five of them were socio-demographic characteristics. Due to limitations on the availability of studies dealing with the issues described above, a group of 24 questions are the items which are adjusted from the previously conducted studies (de Jager & Gbadamosi, 2010;Faganel, 2010;Kitcharoen, 2004;Levitz, Noel, & Richter, 2002;Micari & Pazos, 2012;Noel-Levitz, 2014;Sembiring, 2015;Sultan & Wong, 2010). The questions about BI are in the form of statements which were confirmed in the previously conducted research (Bloemer, de Ruyter, & Wetzels, 1999;Jaroslav Dado et al, 2012;Endres et al, 2009;Hennig-Thurau et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Online academic programs have been shown to have significantly more student dropout and a lack of persistence among their students, a problem postulated upon by many scholars (Gazza & Hunker, 2014;Knestrick et al, 2016;Patterson & McFadden, 2009). Previous research though has demonstrated students who develop a greater sense of connectedness, course satisfaction and higher academic performance are more likely to persist throughout an academic program (Abrami et al, 2011;Sembiring, 2015). Therefore while this study directly measured student's sense of connectedness, satisfaction, learning and actual academic performance, it also measured variables that can significantly affect whether online students develop into self-regulated learners who persist within a course of study and are retained to graduation.…”
Section: Purpose Of Studymentioning
confidence: 99%
“…Research has indicated though that specific student outcomes may be directly related to whether a student chooses to persist within a course of study to graduation. Outcomes such as connectedness, satisfaction, learning and academic performance have all been linked to increased levels of student retention (LaBarbera, 2013;Styron, 2010;Sembiring, 2015).…”
Section: Activating Students As Instructional Resources For Onementioning
confidence: 99%
See 1 more Smart Citation